Package Tour Contracts in Turkish Law - Karaturp, Nüket Evrim (International Journal of Contemporary Economics and Administrative Sciences, 2023)
The changing the understanding of vacation has led people to package tours where all the facilities are provided within a single contract all inclusive, instead of classical-style holidays. Package tours have become preferable because of the opportunities they offer and by saving the consumer from the time and effort spent on planning. However, with the spread of package tours, an increase is observed in legal disputes between the contracting parties. Therefore, examining the legal nature of package tour contracts and determining the rights and obligations of the parties will help in resolving legal disputes that arise in practice. In our study, package tour contracts are examined in terms of their elements, legal nature, parties, contractual form condition, mandatory content, amendments, and termination. Also, suggestions are made for amendments in terms of some provisions.